2022
DOI: 10.1038/s41598-022-26002-7
|View full text |Cite
|
Sign up to set email alerts
|

The fate of visual long term memories for images across weeks in adults and children

Abstract: What is the content and the format of visual memories in Long Term Memory (LTM)? Is it similar in adults and children? To address these issues, we investigated, in both adults and 9-year-old children, how visual LTM is affected over time and whether visual vs semantic features are affected differentially. In a learning phase, participants were exposed to hundreds of meaningless and meaningful images presented once or twice for either 120 ms or 1920 ms. Memory was assessed using a recognition task either immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…This is in agreement with the results outlined in Boucher et al (2016) where children's memory performance was better for concrete than for abstract pictures, marked by larger P600 repetition effects elicited by concrete compared to abstract designs and a more pronounced and localized recruitment of the left frontal region for concrete pictures. This also agrees with results highlighted in Shoval et al (2022) where they established that meaning is important for remembering massive amounts of visual information in adults and in Goujon et al (2022) where they found that semantic information does enhance the encoding and maintaining of images in long-term memory when assessed immediately (but not when assessed after weeks). Building on these findings, our comparative data on children and adults' performance additionally shows that the 'concrete-superiority effect' or the relative advantage conferred by meaningfulness is higher for children.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This is in agreement with the results outlined in Boucher et al (2016) where children's memory performance was better for concrete than for abstract pictures, marked by larger P600 repetition effects elicited by concrete compared to abstract designs and a more pronounced and localized recruitment of the left frontal region for concrete pictures. This also agrees with results highlighted in Shoval et al (2022) where they established that meaning is important for remembering massive amounts of visual information in adults and in Goujon et al (2022) where they found that semantic information does enhance the encoding and maintaining of images in long-term memory when assessed immediately (but not when assessed after weeks). Building on these findings, our comparative data on children and adults' performance additionally shows that the 'concrete-superiority effect' or the relative advantage conferred by meaningfulness is higher for children.…”
Section: Discussionsupporting
confidence: 90%
“…Familiarity may also play a role in modulating performance as a function of age, in that people acquire more familiarity with real-world images as they age. It is also possible that meaningful images, which are more nameable, may be dual-coded (as visual and verbal), whereas meaningless images may be encoded only visually as discussed in Goujon et al (2022) and this strategy may vary between children and adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is supported by the findings of participants first forgetting objects due to their saliency, rather than their meaning, recalling more false objects semantically consistent with the recalled scene over time, and participants forgetting more objects over time. Interestingly, the parallel found in the current study between gist-based processing and the generalization of memory supports the idea that the first information in memory may also the last to leave (Potter, 2012), despite other recent studies challenging this idea (Goujon et al, 2022).…”
Section: Discussionsupporting
confidence: 87%